Dengue knowledge and preventive practices among residents in flat pandan Indah, Ampang Selangor - Ramly, Norfarhana (Universiti Sains Malaysia, 2015)
Dengue classified as an important disease in public health due to the global incidence of dengue has grown dramatically in recent decades. Dengue can cause morbidity and mortality in worldwide imposing a significant economic and disease burden in endemic countries. In Malaysia, dengue has been declared as one of the threat to the public. Ministry of Health (MOH) reported that the number of dengue cases since January until Jun 2014 was 38, 41 1 cases which was higher compared to the number reported in 2013 was 10, 910 cases. Selangor recorded the highest number of dengue cases. The general objective of the study to determine the knowledge and preventive practices of dengue among residents in Flat Pandan Indah, Ampang Selangor. A cross sectional study was conducted on 298 subjects' recruited using convenient sampling method. A validated questionnaire was given to all subjects that fulfilled the inclusion criteria. Demographic data of subjects was analyzed using descriptive statistic. One way anova test was used to check difference between age and level of education with knowledge and practice. Then, independent t-test was used to test the difference of knowledge and practices between gender. Among 298 subjects (n=298), 61.7% had good knowledge regarding dengue but there were 50.3% of the subjects in Flat Pandan Indah had limited extent of dengue. The result found from this study showed no significant difference between age and dengue knowledge but there was association between gender and level of education with dengue knowledge with value of /?<0.05. There was no association between age and level of education with preventive practices of dengue but there is significant association between gender with preventive practices of dengue with the value of p<0.05. There was no correlation between dengue knowledge and preventive practices (r = 0.093). The study reveals that majority of the subjects had good knowledge regarding dengue but the practices to prevent dengue are poor. Thus, health education program on dengue should be done on the community members in the future.